Bridging the Gap: Integrating Sustainability-as-Practice in Japanese Business English Education - Past, Travis; Smith, Michael D. (Journal of Education For Sustainable Innovation, 2025)
This action research sought to investigate the experiences and positions of Japanese college-level learners relating to sustainability to better embed education for sustainable development within departmental-level practice. Specifically, we analyzed the responses of students enrolled in a fourteen-week Business English course designed to prompt reflections and discussions of sustainability in English as a foreign language. Drawing on idiographic action research, data was collected through written reflections and semi-structured interviews throughout the semester, with final group interviews performed upon course completion. Results indicate significant improvement in students’ capacities to reflect upon and discuss sustainability in English. More pointedly, critical awareness of corporate sustainability measures expanded throughout the course. Global pushes for sustainability extend beyond borders, cultures, and languages. Consequently, education for sustainable development should not be confined solely to native language instruction but integrated into second-and-foreign-language courses. Japan, a nation claiming a policy-level commitment to English education and sustainable development, lags in global assessments of English proficiency and in adopting forward-thinking pedagogical approaches designed to enhance sustainable awareness and action. Due to these insufficiencies, Japan’s capacity to collaborate in sustainability efforts may be constrained. Thus, pedagogical initiatives like those detailed here may work to bridge gaps between policy and practice.